Hardiness In Relation to Career Adaptability on Students of Vocational School - Ernawati, Linda; Nurhikmah2, Maida Sari (Academia Edu Cendekia Indonesia (AEDUCIA), 2023)
This study aims to determine whether there is an effect of hardiness on career adaptability in class XII students of SMKN X Garut. The method used in this research is quantitative with a deductive approach. The sampling technique used is a Proportionate Stratified Random Sampling. This research was conducted on class XII students with a total sample size of 251 respondents. Data collection in this study used measuring instruments adapted from Sandy Pratama (2020). The first measuring instrument used the Career Adapt-Abilities Scale (CAAS) (α = 0.926 and validity = 0.543 - 0.865) and the second measuring instrument used the Hardiness scale (α = 0.850 and validity = 0.567 - 0.755). Data analysis used simple linear regression test with the help of Jamovi 1.6.23. The results of the analysis showed an F score of 25.0 with a p-value <0.001 (p-value <0.05) meaning that hardiness affects career adaptability. The contribution of hardiness to career adaptability is R2 = 0.0914 (9.14%). The conclusion is that there is an effect of hardiness on career adaptability in class XII students of SMKN X Garut. Suggestions for the school from this research are to hold activities such as introduction to the world of work, job fairs, trainings so that students can prepare themselves in facing to world of work, and hold hardiness seminars so that students understand how the concept of hardiness.